2022
DOI: 10.2147/prbm.s344624
|View full text |Cite
|
Sign up to set email alerts
|

Linkages Between Transformational Leadership, Work Meaningfulness and Work Engagement: A Multilevel Cross-Sectional Study

Abstract: Purpose The issue of employee engagement has increasingly become a focus of concern in public management practice. Based on the theory of purposeful work behavior, integrative theory of employee engagement and Pratt and Ashforth’s typology of work meaningfulness, this study proposes and examines the mediating effects of two types of meaningfulness between transformational leadership and work engagement and the moderating effects of transformational leadership on the relationship between two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 77 publications
3
24
0
2
Order By: Relevance
“…Teachers' work engagement (WE) is an essential aspect of achieving the success of school organizations. WE is positive psychology experienced by a person, which is reflected in emotional, cognitive and physical involvement in carrying out work enthusiastically and with energy (Meng et al, 2022). Furthermore, employees who have high WE can manage positive energy and inspiration from various activities into useful resources at work (Bakker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' work engagement (WE) is an essential aspect of achieving the success of school organizations. WE is positive psychology experienced by a person, which is reflected in emotional, cognitive and physical involvement in carrying out work enthusiastically and with energy (Meng et al, 2022). Furthermore, employees who have high WE can manage positive energy and inspiration from various activities into useful resources at work (Bakker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research outcomes concluded that transformative leadership is associated with staff member's engagement (Meng et al, 2022). Transformational leaders inspire their staff members to achieve elevated success by establishing a good-looking and thrilling apparition, setting challenging goals, being positive and optimistic and emphasizing group job (Anggiani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To increase work-life balance, the leader must create an open dialogue with employees so that when stress begins to interfere with work, the leader can provide the flexibility needed so that employee work engagement is maintained (Lee et al, 2021). Behavioral theories state that efforts aimed at achieving the desired thing can be translated by external social work characteristics into work meaningfulness that plays a key role in influencing work outcomes (Meng et al, 2022) which of course work engagement effectiveness among employees in the public sector is increasingly a topic of great concern ( Mandu et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For employees in the public sector, the level of work engagement high can push quality of public services (Meng et al, 2022), the government needs employees which provides quality and timely services as form community satisfaction and expectations . For that, leader must understand the most suitable leadership style for implemented by employee's government.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation